Poor Sleep Quality and Factors Among Reproductive-Age Women in Southwest Ethiopia - Bogale, Biruk; Wolde, Asrat; Mohammed, Nuredin; Midaksa, Gachana; Bekele, Bayu Begashaw (Frontiers in Psychiatry, 2022)
Background: Adequate sleep is vital for physical and mental well-being. Sleep-related problems including poor quality of sleep have been increasing throughout the world among reproductive-aged women. However, evidence is scarce regarding poor sleep quality and its predictive factors among women of the reproductive age group in Ethiopia. Objective: To assess sleep quality and associated factors among women of reproductive age group in Mizan Aman town, Southwest Ethiopia. Method: Community-based cross-sectional study was conducted among 606 reproductive-aged women from November to December 2020, in Mizan Aman town. Data were collected using structured interview administered questionnaires. Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality. Multivariable logistic regression was applied using an odds ratio with a corresponding 95% confidence interval to evaluate the statistical significance of predictor variables. Result: The overall prevalence of poor sleep quality was 71.3%. The late age group of 42-49 (AOR, 95% CI; 1.21(1.08-5.76), palpable/visible thyroid gland (AOR, 95% CI; 2. 12 (1.08-3.82), current substance use (AOR, 95% CI; 1.76 (1.11-6.10) and having premenstrual syndrome (AOR, 95% CI; 1.86 (1.38-3.12) were significantly associated with poor sleep quality among reproductive age group women. Conclusion: Two-thirds of the reproductive age group women have poor sleep quality. Therefore, screening of sleep patterns among this particular age group is warranted. Moreover, designing effective health education and promotion considering the identified predictors could be helpful to improve sleep quality